ANALISIS PENDIDIKAN MULTIKULTURAL (STUDI KASUS PADA UNIVERSITAS MUHAMMADIYAH TAPANULI SELATAN) - Muhammad Nuddin; Muslimin Hutapea (STAI Tuanku Tambusai, 2022)
Various efforts have been made by the community to strengthen mutual respect for various cultures, races and even religions among young people, educated and educated people. This aims to strengthen the integrity of the nation and state. Some circles carry out programs to introduce religious teachings so that mutual suspicions do not arise which result in divisions and a lack of mutual understanding between adherents of various beliefs and cultures. One of them is UMTS, a tertiary institution of the Muhammadiyah organization in the Southern Tapanuli region which highly upholds multiculturalism for students by teaching the basic teachings of Islam and Muhammadiyah for students and is included in the category of compulsory subjects to be followed and passed in these courses for various groups of students consisting of from various faculties and study programs within the Muhammadiyah University of South Tapanuli (UMTS).